Polymer-Halloysite Composite Membranes for Ultrafiltration and Proton Exchange Applications - Zhang, Y.; Wang, J.; Zhu, J.; Liu, Y.; Liu, Jian (2017)
© The Royal Society of Chemistry 2017. Significant progress has been achieved in recent years on the development of halloysite nanotubes with the purpose of improving the membrane performance. In this chapter, polymer-halloysite composite membranes for ultrafiltration and proton exchange applications were highlighted. Additionally, the challenges in the fabrication of halloysite nanotubes based on the membranes and future prospects are presented as well.